First case of disseminated cryptococcosis in a Gorilla gorilla. Issue 11 (25th June 2014) - Mischnik, Alexander; Stockklausner, Julia; Hohneder, Nicole; Jensen, Henrik E.; Zimmermann, Stefan; Reuss, David E.; Rickerts, Volker; Tintelnot, Kathrin; Stockklausner, Clemens
Summary In humans, Cryptococcus mainly infects individuals with HIV infection or other types of immunosuppression. Here, we report the first case of disseminated cryptococcosis in a simian immunodeficiency virus‐negative 27‐year‐old female Gorilla gorilla presenting with lethargy, progressive weight loss and productive cough. The diagnosis was confirmed by positive lung biopsy culture, serum cryptococcal antigen, and cerebral histopathology demonstrating encapsulated yeasts. Molecular characterisation of lung culture isolate yielded Cryptococcus neoformans var. grubii. An immune‐deficiency could not be demonstrated.